Regulatory Effect of Iguratimod on the Balance of Th Subsets and Inhibition of Inflammatory Cytokines in Patients with Rheumatoid Arthritis - Yunzhi Xu; Qi Zhu; Jinglve Song; Hongli Liu; Yutong Miao; Fan Yang; Feiyan Wang; Wenjing Cheng; Yebin Xi; Xiaoyin Niu; Dongyi He; Guangjie Chen (Mediators of Inflammation)
Objective. To expand upon the role of iguratimod (T-614) in the treatment of rheumatoid arthritis (RA), we investigated whether the Th1, Th17, follicular helper T cells (Tfh), and regulatory T cells (Treg) imbalance could be reversed by iguratimod and the clinical implications of this reversal. Methods. In this trial, 74 patients were randomized into iguratimod-treated (group A) and control (broup B) group for a 24-week treatment period. In the subsequent 28 weeks, both groups were given iguratimod. Frequencies of Th1, Th17, Tfh, and Treg were quantified using flow cytometry, and serum cytokines were detected by enzyme-linked immunosorbent assay. mRNA expression of cytokines and transcriptional factor were quantified by RT-PCR. The composite Disease Activity Score, erythrocyte sedimentation rate, and C-reactive protein were assessed at each visit. Result. The clinical scores demonstrated effective suppression of disease after treatment with iguratimod. In addition, iguratimod downregulated Th1, Th17-type response and upregulated Treg. Furthermore, the levels of Th1, Th17, and Tfh associated inflammatory cytokines and transcription factors were reduced after treatment with iguratimod, while the levels of Treg associated cytokines and transcription factors were increased.